High-pressure granulites from Carire, Borborema Province, NE Brazil: Tectonic setting, metamorphic conditions and U-Pb, Lu-Hf and Sm-Nd geochronology - Amaral, Wagner da Silva; dos Santos, Ticiano Jose Saraiva; Wernick, Eberhard [UNESP]; Nogueira Neto, Jose de Araujo; Dantas, Elton Luiz; Matteini, Massimo (Elsevier B.V., 2012)
In the northwest region of the Ceara Central Domain, Borborema Province, an elongate area of mylonitic diorites and granodiorites is structurally controlled by NE-SW-trending strike-slip faults. Granitic material and layers and lenses of felsic and mafic granulites occur along the main shear zones. We present and discuss petrographic, geothermobarometric. and geochronological (LA-MC-ICPMS U-Pb and Lu-Hf in zircon and Sm-Nd whole-rock) data for these rocks. Felsic granulites are composed of orthopyroxene + clinopyroxene + plagioclase + quartz +/- hornblende +/- garnet +/- biotite +/- feldspar, while the mafic granulites comprise clinopyroxene + plagioclase + garnet + hornblende +/- rutile +/- quartz. The P-T conditions recorded range from 9.4 to 83 kbars and from 804 to 870 degrees C for the felsic granulites and from 13.6 to 10.2 kbars and 910 to 750 degrees C for the mafic granulites. U-Pb zircon ages of granodiorite host rocks are 2157 and 2044 Ma. The felsic granulites yield a U-Pb age of 2110 Ma, while the mafic granulites yield U-Pb zircon ages of 613 and 589 Ma for the metamorphic recrystallization. Sm-Nd and Lu-Hf T-DM ages for the mafic granulites are similar (1.6-1.3 Ga) and share positive values of epsilon(Nd) and epsilon(Hf), which suggests that these mafic rocks were derived from a juvenile Mesoproterozoic crust. In addition, the felsic granulites and the granodiorites have similar TDM-Nd and U-Pb ages (with positive values of epsilon(Nd)), indicating a Paleoproterozoic mantle source for these rocks. (C) 2012 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.
Keywords: Granulites; High pressure; Metamorphic conditions; U-Pb; Borborema Province